Do OECD countries cheat with their national tax revenue forecasts? - Beate Regina Jochimsen; Robert Lehmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Nowadays, a solid budget serves as an important quality signal for the electorate. Therefore, politicians might face an incentive to influence tax revenue forecasts which are widely regarded as a key element for budget setups. Looking at the time period from 1996 to 2012, we systematically analyze whether national tax revenue forecasts in 18 OECD countries are biased through political distortions. Based on several theoretical approaches drawn from the theories of political economy, we test four hypotheses using panel estimation techniques. We find strong support for partisan politics. Left governments seem to overestimate tax revenues more than right ones to satisfy their electorate with additional expenditure plans. Contrary to the theoretical prediction based on the common pool problem, we find that more fragmented governments and parliaments tend to produce more pessimistic tax revenue forecasts. One reason might be that at least one of the incumbents will stay in office and will be part of the next government, too. We do not find empirical evidence for political business cycles or an influence of the reelection probability on tax revenue forecasts at all.
Keywords: H11; H68; P16; 330